2019
DOI: 10.1002/bit.26902
|View full text |Cite
|
Sign up to set email alerts
|

A three‐dimensional microfluidized liver system to assess hepatic drug metabolism and hepatotoxicity

Abstract: In this study, we propose the design and fabrication of a liver system on a chip. We first chose the most suitable three‐dimensional liver‐like model between cell spheroids and microtissue precursors, both based on the use of hepatocellular carcinoma cells (HepG2) to provide proof‐of‐concept data. Spheroids displayed high cell density but low expression of the typical hepatic biomarkers, whereas microtissue precursors showed stable viability and function over the entire culture time. The two liver‐like models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 66 publications
1
33
0
Order By: Relevance
“…The liver‐on‐a‐chip systems have also been utilized for hepatotoxicity evaluation of various drugs or toxicants used in a high‐throughput manner . In addition, a perfusable liver‐on‐a‐chip model integrated with gelatin‐porous microbeads was constructed to evaluate ethanol‐induced cytotoxicity, providing a potential platform for drug development and toxicity research …”
Section: Hydrogels In Organs‐on‐a‐chip Engineeringmentioning
confidence: 99%
“…The liver‐on‐a‐chip systems have also been utilized for hepatotoxicity evaluation of various drugs or toxicants used in a high‐throughput manner . In addition, a perfusable liver‐on‐a‐chip model integrated with gelatin‐porous microbeads was constructed to evaluate ethanol‐induced cytotoxicity, providing a potential platform for drug development and toxicity research …”
Section: Hydrogels In Organs‐on‐a‐chip Engineeringmentioning
confidence: 99%
“…HepG2 cells were cultured on GPMs in spinner flasks (Integra), as previously reported with slight modifications (Corrado et al, 2019). Briefly, 35 mg of GPMs were loaded with 5.25 × 10 6 cells (30 cell/GPM ratio).…”
Section: Hepg2-µtps Developmentmentioning
confidence: 99%
“…With the perspective of elucidating the inter-organs crosstalk with a more physiological functional 3D tissues, we reported a development of a novel Intestine-Liver-on-Chip (InLiver-OC) consisting of two directly interconnected chambers (Intestine-compartment and Liver-compartment) that enable the culture of a 3D Human Intestine Model (3D-HIM) as well as 3D liver microtissues (HepG2-µTPs) in order to simulate the physiological mechanism of the first-pass metabolism of orally-ingested compounds. Bottom-up approach was used to fabricate the 3D-HIM provided with an endogenous ECM (Imparato et al, 2013) and HepG2-µTPs, as previously reported (Corrado et al, 2019). The combination of such physiological relevant 3D models with microfluidic technology allowed us to investigate the protective role of the intestine on liver injury, analyzing the 3D-HIM hyper-permeability as well as the intestinal stroma remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Good news from the field of skin regeneration: the work on bioengineered skin substitutes has been selected by the editorial board as the cover story of the issue of December 2019 (www.mdpi.com/2077-0383/8/12). The article, presented by a group active in the field of dermal substitutes [13] and three-dimensional tissue-like models [14], is focused on the analysis of the most Cancer, and more specifically the usage of nanoparticles (NP) both for multimodal imaging and as contrast agents (CAs), is the topic of a review [8] which highlights the advantages of using NP-based PET/MRI multimodal imaging in tumor diagnosis and characterization. Additionally, these nanosystems can be applied to theranostics in the very prominent scenario of personalized medicine.…”
mentioning
confidence: 99%
“…Good news from the field of skin regeneration: the work on bioengineered skin substitutes has been selected by the editorial board as the cover story of the issue of December 2019 (www.mdpi.com/ 2077-0383/8/12). The article, presented by a group active in the field of dermal substitutes [13] and three-dimensional tissue-like models [14], is focused on the analysis of the most modern strategies to overcome the scarring process and promote skin regeneration, by implanting an engineered dermis capable of recapitulating the architecture and presenting molecular signals similarly to the native dermis [10].…”
mentioning
confidence: 99%